2016
DOI: 10.1152/ajpheart.00501.2016
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the muscle metaboreflex and the arterial baroreflex in control of arterial pressure and skeletal muscle blood flow

Abstract: The muscle metaboreflex and arterial baroreflex regulate arterial pressure through distinct mechanisms. During submaximal exercise muscle metaboreflex activation (MMA) elicits a pressor response virtually solely by increasing cardiac output (CO) while baroreceptor unloading increases mean arterial pressure (MAP) primarily through peripheral vasoconstriction. The interaction between the two reflexes when activated simultaneously has not been well established. We activated the muscle metaboreflex in chronically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…While studies examining interactions between the EPR and the baroreflex (Kaur et al 2016;Hureau et al 2018) and between the CR and the baroreflex (Katayama et al 2014(Katayama et al , 2016 have revealed interactive influences on the circulatory response to exercise, investigations on the haemodynamic consequences of the EPR:CR interaction are scarce and rather indirect. McCoy and colleagues (1987) found the EPR-evoked increases in blood pressure to inhibit the discharge of aortic chemoreceptors in anaesthetised cats.…”
Section: Introductionmentioning
confidence: 99%
“…While studies examining interactions between the EPR and the baroreflex (Kaur et al 2016;Hureau et al 2018) and between the CR and the baroreflex (Katayama et al 2014(Katayama et al , 2016 have revealed interactive influences on the circulatory response to exercise, investigations on the haemodynamic consequences of the EPR:CR interaction are scarce and rather indirect. McCoy and colleagues (1987) found the EPR-evoked increases in blood pressure to inhibit the discharge of aortic chemoreceptors in anaesthetised cats.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the current study cannot sufficiently address the exact nature of the interaction (additive, occlusive or facilitative) between these two reflexes, which is intimately dependent on the haemodynamic parameter being investigated (Kaur et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the baroreflex nearly completely prevents the metaboreflex from causing substantial peripheral vasoconstriction. As workload rises, the skeletal muscle vasculature progressively becomes the largest fraction of the total vascular conductance and therefore substantial pressor responses via peripheral vasoconstriction could only occur via constriction of the active muscle (O’Leary, 1991; Kaur et al, 2016, 2018). This could engender a positive feedback, vicious cycle where further metaboreflex activation causes further skeletal muscle vasoconstriction.…”
Section: Baroreflex – Metaboreflex Interaction In Hypertensionmentioning
confidence: 99%
“…This could engender a positive feedback, vicious cycle where further metaboreflex activation causes further skeletal muscle vasoconstriction. Indeed, recent studies have shown that there is some vasoconstriction within the active skeletal muscle during metaboreflex activation and this serves as an amplifier of the original response (Kaur et al, 2016). After induction of HF, this vasoconstriction in skeletal muscle is substantially greater perhaps due to depressed ability of the baroreflex to buffer metaboreflex-induced peripheral vasoconstriction (Kim et al, 2005a; Kaur et al, 2018).…”
Section: Baroreflex – Metaboreflex Interaction In Hypertensionmentioning
confidence: 99%